What makes performance-related pay schemes work? Finnish evidence - Antti Kauhanen; Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2004)
We analyze how features of performance-related pay (PRP) schemes affect their perceived motivational effects using a Finnish survey from 1999. The results show that the following features are important for a successful PRP scheme: (i) the employees have to feel they are able to affect the outcomes; (ii) the organizational level of the performance measurement should be close to the employee: individual and team level performance measurements increase the probability that the scheme is perceived to be motivating; (iii) employees should be familiar with the performance measures; (iv) the level of payments should be high enough and rewards frequent enough. Low PRP levels do not generate positive effects; (v) the employees should participate in the design of the PRP scheme. – – Tarkastelemme kuinka tulospalkkausjärjestelmien piirteet vaikuttavat niiden koettuun kannustavuuteen käyttäen suomalaista kyselyaineistoa vuodelta 1999. Tulokset osoittavat, että seuraavat piirteet ovat tärkeitä kannustavalle tulospalkkausjärjestelmälle: (i) työntekijöiden täytyy voida vaikuttaa toiminnan tuloksiin; (ii) suoritusmittaus tulisi tapahtua henkilökohtaisella tasolla tai tiimitasolla; (iii) työntekijöiden tulisi tuntea suoritusmittarit; (iv) tulospalkkioiden tason tulisi olla riittävän korkea ja niitä tulisi maksaa riittävän usein. Mikäli tulospalkkioiden taso on alhainen, vaikutuksia koettuun kannustavuuteen ei ole; (v) työntekijöiden tulisi osallistua tulospalkkausjärjestelmän suunnitteluun.
Keywords: 330; Leistungsorientierte Vergütung; Finnland